2014
DOI: 10.5037/jomr.2014.5104
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Formation, Severity and Location of White Spot Lesions during Orthodontic Treatment with Fixed Appliances

Abstract: ObjectivesThe purpose of the present study was to investigate factors affecting the formation, severity and location of white spot lesions in patients completing fixed appliance therapy.Material and MethodsA total of 45 patients (19 males and 26 females, mean age 15.81 years, standard deviation 2.89 years) attending consecutively Aberdeen Dental Hospital (ADH) between January and June 2013 to have their fixed appliances removed were given a questionnaire to elicit information regarding their dental care and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 41 publications
4
69
2
9
Order By: Relevance
“…In the present study, we observed higher caries activity among patients undergoing fixed orthodontic treatment, and caries activity increased with treatment length leveling off after 2 years. This last finding is in disagreement with previous long-term follow-up studies [Richter et al, 2011;Khalaf, 2014]. Richter et al [2011] found that the number of NCL increased from 3.0 to 5.3 after 22 and 33 months of treatment, respectively.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…In the present study, we observed higher caries activity among patients undergoing fixed orthodontic treatment, and caries activity increased with treatment length leveling off after 2 years. This last finding is in disagreement with previous long-term follow-up studies [Richter et al, 2011;Khalaf, 2014]. Richter et al [2011] found that the number of NCL increased from 3.0 to 5.3 after 22 and 33 months of treatment, respectively.…”
Section: Discussioncontrasting
confidence: 57%
“…However, these studies have important shortcomings, such as lack of a control group [Ahmed et al, 2011], exclusion of upper molars and lower teeth on caries examination [Tufecki et al, 2011], and follow-up restricted to 12 months [Ahmed et al, 2011;Tufekci et al, 2011;Lucchese and Gherlone, 2013]. Studies with longer follow-up periods up to 2 or 3 years have used pre-and posttreatment photographs for caries assessment, which may compromise caries detection [Richter et al, 2011;Khalaf, 2014].…”
mentioning
confidence: 99%
“…Desta forma, recomenda-se intensa secagem da estrutura dental antes do exame para que mesmo áreas com pequenas perdas minerais se tornem evidentes. Tão importante quanto identificar as manchas brancas é diferenciá-las de outras manchas que também podem se apresentar com aspecto esbranquiçado como fluorose leve que acomete grupos de dentes, atingindo da cervical até a incisal -e as hipoplasias de esmaltenormalmente resultado de traumas dos dentes decíduos que afetam os permanentes, redondas ou ovais, sendo mais comuns no terço médio e incisal (17,18,19).…”
Section: Protocolounclassified
“…The prevalence of white spot lesions after these treatments varies between 2% and 96% [4]. Approximately 50% of patients treated with fixed appliances develop at least one white spot lesion [5], usually after 1 month of using the fixed orthodontic [6]. Mattousch et al found that the white spot lesions appearing after completion of a fixed orthodontic treatment were irreversible unless specially treated.…”
Section: Introductionmentioning
confidence: 99%